Role of 70% Alcohol in Halal Disinfectant Used - Nurjannah Nurjannah; Syamsul Bakhri; Irma Nur Afiah; Resky Alqadri R; Rizka Yanti Ramli (Universitas Muslim Indonesia, 2021)
At the end of 2019, a new disease caused by a virus emerged and attacked the respiratory system, this disease is known as the novel coronavirus disease 2019 (Covid-19). Covid-19 can spread through particles from the sufferer's sneeze or cough that stick to other objects such as clothing or electronic devices from surrounding people. Covid-19 first spread very rapidly in China and is currently spreading to other parts of the country. This pandemic is one of the things that people are worried about, but it can prevent various things. There are many ways to prevent the transmission of Covid-19, one of which is by using disinfectants. Disinfectants are chemicals used to kill or reduce the number of unwanted microorganisms, such as bacteria, fungi, and viruses. One of the active ingredients that is often used in making disinfectants is alcohol. Alcohol is effective against both Gram positive and Gram negative including resistant pathogens such as Methiciline Resistant Staphylococcus Aureus (MRSA) and Vancomicin Resistant Enterococci (VRE), Micobacterium tuberculosis, and various other fungi and viruses. The purpose of this paper is to see the halal use of disinfectants that use alcohol. This disinfectant is made in several stages, namely first 50 mL of 99.8% acetic acid with 250 mL of distilled water and 700 mL of 98% alcohol into a stirred tank. The stirring motor is turned on and the mixture is stirred for 15-20 minutes. While stirring add 50 mL of liquid soap (sunlight). To get the desired disinfectant content. After 15-20 minutes the stirring tank is turned off and the disinfectant product is ready for use. The purpose of making this disinfectant is as an ingredient for the spraying process as a preventive measure against the coronavirus, killing or inhibiting the proliferation of bacteria and viruses. As well as efforts to improve hygiene to prevent the spread of the Coronavirus (Covid-19). One of the steps is spraying in vital places or public facilities. This disinfectant spraying work program is useful to anticipate the spread of the Covid-19 virus. In addition, this activity is expected to provide comfort to the community, especially in the South Sulawesi area in doing outdoor activities. In connection with the above, the use of disinfectants containing alcohol is allowed or lawful to use.